Investigating the Antioxidant Properties of Royal Jelly and Vitamin C on Enzymes, Histomorphometric and Liver Cells Apoptosis in Mice Suffering Hemolytic Anemia - Hojat Anbara; Rasoul Shahrooz; Hasan Malekinejad; Sadeq Saadati (Fasa University of Medical Sciences, 2016)
Background & Objective: Hemolytic anemia induced by phenylhydrazine (PHZ) as a hemolytic composition can change the function and structure of liver. Therefore, the present study attempts to evaluate the protective effects of vitamin C and royal jelly co-administration against the oxidative damages and liver apoptosis induced by hemolytic anemia in adult mice. Materials & Methods: 32 adult male mice were divided equally and randomly into four groups. The first group received normal saline with a dose of 0.1 ml, IP. The second group received a dose of vitamin C (250 kg/mg, IP) along with 100 kg/mg dose of royal jelly administered orally. The third group was administered with 6 mg/100 gr, IP phenylhydrazine in 48 hour intervals. Finally, the fourth group received vitamin C and royal jelly in the doses similar to the first three groups along with phenylhydrazine with the same doses of previous groups. After 35 days, the serum and testis samples were taken and were used for serum analysis and histochemical and histomorphometric studies. Results: Phenylhydrazine increased the level of serum concentration of aspartate transaminase, alkaline phosphatase, alanine transaminase, malondialdehyde and lactate dehydrogenase and decreased the superoxide dismutase along with the total antioxidant capacity and serum albumin. Moreover, phenylhydrazine increased the apoptosis, the number of kupffer cells and the diameter of hepatocytes. Prescribing the royal jelly with vitamin C improved the changes of abovementioned parameters significantly. Conclusion: Royal jelly with vitamin C is an antioxidant with the potential properties in preventing the oxidative damages and apoptosis induced by phenylhydrazine-induced hemolytic anemia in mouse liver.